Media Pembelajaran Interaktif 2D untuk Mata Pelajaran Matematika Bangun Ruang - Verdian, Ihsan (Fakultas Komputer - Universitas Universal, 2024)
The focus of this research is on designing an alternative interactive 2D learning media specifically for plane geometry for students. The goal is to provide an interactive learning media option on geometry at school. The plane geometry material is combined with 2D interactive media using interactive learning media and Game Development Life Cycle (GDLC) methods. This learning media integrates plane geometry content, game scenarios, and interactive elements to create an engaging and realistic learning experience. The expected outcome of this research is an engaging learning media for students to learn plane geometry and to facilitate educators in delivering this material effectively.